2020
DOI: 10.21203/rs.3.rs-19454/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of service satisfaction and associated status among women who have given birth in Adigrat general hospital, Ethiopia, 2018.

Abstract: Background: The study aimed to assess the satisfaction of service delivery and the associated status among women who gave birth to Adigrat general hospital, Ethiopia, 2018. Methods: Institutional based cross-sectional study design was conducted in Adigrat hospital from February to March 2018. Interviews with interviewed using structured questionnaires of 302 systematic women who were born at general hospital. The information is submitted to EPI-info version 7.2 and exported to SPSS version 20 for analysis. Sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…1,12,17,18,20,29,30,32,34,37 Seven of the studies were from Southern Nations, Nationalities, and Peoples Representative (SNNPR) region, 6,8,14,16,23,35,36 and 5 in Addis Ababa. 11,25,33,38,53 The remaining three studies were from Harar, 26 Tigray, 22 and Afar region. 54 The studies conducted in the SNNPR region 14 and Addis Ababa, 11 respectively, reported the highest, 95%, and the lowest, 19%, level of women’s satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,12,17,18,20,29,30,32,34,37 Seven of the studies were from Southern Nations, Nationalities, and Peoples Representative (SNNPR) region, 6,8,14,16,23,35,36 and 5 in Addis Ababa. 11,25,33,38,53 The remaining three studies were from Harar, 26 Tigray, 22 and Afar region. 54 The studies conducted in the SNNPR region 14 and Addis Ababa, 11 respectively, reported the highest, 95%, and the lowest, 19%, level of women’s satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of maternal satisfaction ranges from 18% 11 to 95%, 14 which shows a great variation across different geographical areas and periods. Regarding the associated factors, several factors such as maternal age, 12,1519 residence place, 14,1922 educational status, 1,12,14,16,17,2327 Ante-Natal Care (ANC) utilization, 6,12,14,15,18,21,24,26 status of pregnancy, 12,14,18,25,28,29 maternal outcome, 25,28,30,31 presence of waiting area, 18,22,28,32 presence of a clean toilet, 12,18,22,27,33 having a plan to delivery at health facility, 1,3,12,17,22,26,34,35 waiting time to be seen by obstetric caregivers(OCGs), 1,12,…”
Section: Introductionmentioning
confidence: 99%